A multi-scale homogenization model for fine-grained porous viscoplastic polycrystals: II – Applications to FCC and HCP materials. (June 2018) - Song, Dawei; Ponte Castañeda, P.
Abstract: In Part I of this work (Song and Ponte Castañeda, 2018a), a new homogenization model was developed for the macroscopic behavior of three-scale porous polycrystals consisting of random distributions of large pores in a fine-grained polycrystalline matrix. In this second part, the model is used to investigate both the instantaneous effective behavior and the finite-strain macroscopic response of porous FCC and HCP polycrystals for axisymmetric loading conditions. The stress triaxiality and Lode parameter are found to have significant effects on the evolution of the substructure, which in turn have important implications for the overall hardening/softening behavior of the porous polycrystal. The intrinsic effect of the texture evolution of the polycrystalline matrix is inferred by appropriate comparisons with corresponding results for porous isotropic materials, and found to be significant, especially at low triaxialities. In particular, the predictions of the model identify, for the first time, two disparate regimes for the macroscopic response of porous polycrystals: a porosity-controlled regime at high triaxialities, and a texture-controlled regime at low triaxialities. The transition between these two regimes is found to be quite sharp, taking place between triaxialities of 1 and 2.